The Roman Conquest of Hispania Citerior. Strategies and Archaeological Evidence in the North-Eastern Peninsular Area. (II-I BCE): the Examples of Puig Castellar of Biosca and Can Tacó (Catalonia, Spain) - Rodrigo Requena, Esther; Romaní Sala, Núria (Collectanea Philologica, 2022)
The aim of this paper is to provide data for the knowledge of the strategies followed by Rome to take effective control of the Citerior Province of Hispania during the 2nd century BC. We will analyse two settlements of the north-eastern region, namely Puig Castellar de Biosca (Province of Lleida) and Can Tacó (Province of Barcelona), that will serve to gauge the degree of Roman territorial implementation and under what forms this power will be consolidated. The period that interests us ranges from the end of the second Punic-Roman conflict to the first decades of the 1st century BC. It was a slow process in which Rome did not have a pre-established plan of action but was adapting its strategy to the different circumstances and stages of the conquest. The end of all this was the final control and pacification of the country. While all the researchers have a common understanding that during the first phase of control of the Hispanic territories the army played the most important role, the main discrepancies are related to the nature and characteristics of this occupation. The main focus in this discussion has its centre in the need to define how the Roman Army embodied his presence in Hispania during the first century of conquest and to characterise the different settlements in order to identify and determine with precision their military character or their connection with the process of conquest without a strictly military function. Funding: This research was funded by the Spanish Ministry of Science, Innovation and Universities (De la consolidación del poder militar romana a la fundación de ciudades (mediados del siglo II a.C.-principios del siglo I d.C). en la Cuenca del rio Segre: Iesso y Iulia Libica DGYCIT PID2019-104120GB-I00-2023-2021), and the Department of Culture of the Catalan Autonomous Government (La conquesta romana a la Catalunya interior: l’exemple de Puig Castellar (Biosca), CLT009/18/00014).